A contemporary look at allergic conjunctivitis - Pascale Dupuis (Allergy, Asthma & Clinical Immunology, 2020)
Abstract Allergic eye disease is common, yet often overlooked in North America. In the U.S., up to 40% of the population is deemed to be affected and this number is growing. Symptoms and signs of ocular allergy can lead to decreased productivity and negatively impact quality of life (QoL). Various treatment options exist to achieve symptom control. For allergic conjunctivitis, ophthalmic agents include antihistamines, mast cell stabilizers, dual-activity agents, nonsteroidal anti-inflammatory drugs (NSAIDs), steroids and some off-label treatments. Immunotherapy is recommended as a therapeutic option. This review provides a summary of the forms of ocular allergies, with a focus on symptoms and signs, impact on QoL, physical examination, diagnosis and therapeutic options of allergic conjunctivitis. Through multidisciplinary collaborations, a simplified algorithm for the treatment of allergic conjunctivitis is proposed for Canadian clinical practice.